2023
DOI: 10.1037/pro0000497
|View full text |Cite
|
Sign up to set email alerts
|

Multiple microaggressions and therapy outcomes: The indirect effects of cultural humility and working alliance with Black, Indigenous, women of color clients.

Abstract: We investigated the association between racial microaggressions and microaggressions against women in therapy and positive therapy outcomes. We also tested the potential intervening roles of cultural humility and working alliance in these associations. Participants were a sample of Black, Indigenous, Women of Color (BIWOC; N = 288) who had been in therapy. The sample indicated initial symptom severity and completed the Racial Microaggressions in Counseling Scale, Microaggressions against Women Scale, Cultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Relatedly, higher therapist cultural humility continued to predict a stronger working alliance when accounting for missed cultural opportunities. This supports the MCO literature linking higher therapist cultural humility to stronger working alliance (Davis et al, 2018; DeBlaere et al, 2023; Grad, 2022; Hook et al, 2013, 2017; Owen et al, 2014) and fewer missed cultural opportunities (Owen et al, 2016, 2017).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Relatedly, higher therapist cultural humility continued to predict a stronger working alliance when accounting for missed cultural opportunities. This supports the MCO literature linking higher therapist cultural humility to stronger working alliance (Davis et al, 2018; DeBlaere et al, 2023; Grad, 2022; Hook et al, 2013, 2017; Owen et al, 2014) and fewer missed cultural opportunities (Owen et al, 2016, 2017).…”
Section: Discussionsupporting
confidence: 83%
“…The MCO framework is comprised of three constructs: (a) cultural humility (i.e., a relational, other-oriented approach marked by a therapist’s curiosity, openness, and nonsuperiority; Hook et al, 2013; Owen, 2013; Tervalon & Murray-García, 1998), (b) cultural opportunities (i.e., a therapist’s identification of and response to therapeutic cultural markers during session; Owen, 2013; Owen et al, 2016), and (c) cultural comfort (i.e., the degree to which a therapist feels at ease, or lack thereof, when engaging in cultural conversations; (Owen et al, 2017; Pérez-Rojas et al, 2019). Clients who perceive their therapist as more culturally humble report therapists missing fewer cultural opportunities during sessions (Owen et al, 2016), better outcomes (Hook et al, 2013; Kivlighan & Chapman, 2018; Owen et al, 2016), stronger working alliance (DeBlaere et al, 2023; Hook et al, 2013, 2017), and experiencing fewer microaggressions in therapy (Davis et al, 2016; Hook et al, 2016). Clients who perceive their therapist as less attentive to exploring cultural opportunities during sessions (i.e., more missed opportunities) report a weaker working alliance and lower treatment outcomes (Davis et al, 2018; Hook et al, 2013; Owen et al, 2016, 2017).…”
mentioning
confidence: 99%
“…Norcross and Lambert (2018) found that in 306 studies, including over 30,000 clients, the therapeutic alliance had a medium effect counseling outcome in individual counseling ( r = 0.28, d = 0.57). Consistent with common factors literature (e.g., Hubble et al., 2010), the quality of TWA between client and counselor may differ based on client characteristics (e.g., race and ethnicity, gender, and age; DeBlaere et al., 2022; Owe et al., 2011; Vasquez, 2007). Further, clients’ perceptions of the TWA may be developed in a short period of time and remain stable (Horvath & Symonds, 1991) or change over time (Cheng et al., 2021).…”
Section: Twamentioning
confidence: 66%
“…Owen et al, 2019). Importantly, clients who rate their therapist higher on cultural humility, one of the MCO pillars, report fewer microaggressions (Davis et al, 2016; DeBlaere et al, 2023). Thus, it is imperative to develop methods to equip therapists to effectively work with cultural elements in therapy.…”
Section: The Present Studymentioning
confidence: 99%